(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
A radio geometric mean graceful labeling of a connected graph G is a bijection µ from a vertex set V(G) to 1, 2, 3, …, |V(G)| such that for any two distinct vertices u and v of G, . A graph which admits radio geometric mean graceful labeling is called radio geometric mean graceful graph. In this paper, we investigate the radio geometric mean graceful labeling on degree splitting of some graphs